The Prevalence of Sexual Violence in Higher Education Institutions based on Witness Testimony - Hapsari, Iriani indri; Deasyanti; Fellianti Muzdalifah (Universitas Medan Area, 2023)
This research aims to assess the prevalence of sexual violence in higher education as initial exploratory data based on data from witnesses or individuals who have seen or are aware of sexual violence in the campus academic community. Respondents in this research were lecturers, students, education staff, the public in a university environment with a total of 101 respondents who had seen or been witnesses to sexual violence. This research uses incidental sampling. The methodology used is a descriptive quantitative method. Data analysis using SPSS 24. Victims of sexual violence are dominated by women, most sexual violence occurs in verbal and physical form, most sexual violence occurs outside the campus environment compared to inside campus even though the victims are campus academics, The implication of this research is education and awareness of the academic community regarding the prevention and handling of sexual violence in higher education, especially students so that they do not become victims. Apart from that, witnesses of sexual violence should be more courageous in reporting sexual violence and voicing for a campus more that is safe and free from sexual violence.